2011
DOI: 10.1007/s12325-011-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary plasmacytomas in the context of multiple myeloma

Abstract: Plasmacytoma is a frequent complication of multiple myeloma, either at diagnosis or within disease progression. The extramedullary disease confers a poorer prognosis and is biologically distinct with high-risk molecular and histological features, being resistant to conventional treatments. Radiation therapy remains the most effective treatment for extramedullary lesions to achieve local control. There are very limited data from randomized trials regarding the most appropriate systemic treatment. Case reports s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Further studies are required to find a suitable treatment of this condition. 10 To our knowledge, only three similar cases of bilateral ovarian involvement simulating a Krukenberg tumor have been reported up to now, so the present case is the fourth. 6 A B…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Further studies are required to find a suitable treatment of this condition. 10 To our knowledge, only three similar cases of bilateral ovarian involvement simulating a Krukenberg tumor have been reported up to now, so the present case is the fourth. 6 A B…”
Section: Discussionmentioning
confidence: 62%
“…Some series recommend lenalidomide combined with dexamethasone, but there is little data on its efficacy. Further studies are required to find a suitable treatment of this condition 10 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that extramedullary progression of MM is associated with a worse prognosis (5,6). In fact, patients with EMD at the time of the diagnosis, despite a lower International Scoring System (ISS) score, have poorer outcome regardless of first-line treatment (14). For de novo EMD patients who are eligible for stem cell transplantation, a triplet induction therapy approach (bortezomiblenalidomide-dexamethasone) is suggested, followed by high-dose melphalan with autologous haematopoietic cell transplantation, triplet consolidation therapy (bortezomiblenalidomide-dexamethasone), and maintenance treatment consisting of at least lenalidomide (15).…”
Section: Discussionmentioning
confidence: 99%
“…Extramedullary hematopoiesis exists in different tissues and it is frequently correlated with myelopoiesis [Oliveira et al, 2007;Aguado et al, 2011;Muench et al, 2011]. Inside the peritoneal cavity, extramedullary hematopoiesis has been associated with case reports and clinical disorders.…”
Section: Discussionmentioning
confidence: 99%